A Review of the Studies on the Development of Concepts of Decimals and Fractions in Japanese Elementary School Children - Uchida, Akitoshi (Advances in Social Sciences Research Journal, 2020)
It reviewed the studies on the development of the concept of decimals and fractions in Japanese children published in Japan. The Google Scholar search using the keywords "concept of decimals" and "concept of fractions" hit 59 articles published during 1982-2020 in Japan. According to the Course of Study, the guideline for elementary school education in Japan, set by the Ministry of Education, Culture, Sports, Science and Technology (MEXT) of Japan, decimals and fractions should be taught at Arithmetic classes of elementary schools. However, only 17 studies explored the concepts of decimals and fractions and the development of those concepts of primary school children. Moreover, none of them conducted utilizing a scientific research method with empirical data of Japanese elementary school children. It concluded that the research on the education of ratio, including decimals and fractions, in Japan was still in "the stone age" without utilizing genuine scientific methods. (148 words)